Phase diagram of the Eu–H system at high temperatures and high hydrogen pressures. (March 2015) - Saitoh, Hiroyuki; Machida, Akihiko; Matsuoka, Takahiro; Aoki, Katsutoshi
Abstract: The phase boundary between the hydrogen rich phases EuH x >2 -III and EuH x −3 -IV is determined by x-ray diffraction and infrared absorption measurements. Phase IV is characterized as a high temperature phase of phase III over an investigated pressure range of 4– 10 GPa. The transition temperature exhibits a maximum value of 550 K at 7 GPa, where the slope of the boundary switches from positive to negative. The III– IV phase transition is likely accompanied by hydrogen absorption and a resulting valence change of the Eu cation: EuH2.2 (divalent)→EuH3 (trivalent). The small volume change associated with this transition is interpreted as the volume expansion due to hydrogen absorption being compensated by volume contraction due to the Eu 2+ – Eu 3+ valence change. This compensation is considered to be a characteristic feature of rare-earth metals with localized f -electrons. Highlights: The phase boundary between EuH x >2 -III and EuH x −3 -IV is determined. The transition temperature exhibits a maximum value of 550 K at 7 GPa. The volume expansion by hydrogenation is compensated by the Eu 2+ – Eu 3+ valence change.